2021
DOI: 10.1159/000514583
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Dermoscopy for the Recognition of Malignant Collision Tumors

Abstract: <b><i>Background:</i></b> Preoperative diagnosis of malignant collision tumors (MCT) is extremely difficult. The value of dermoscopy to improve the correct detection of these tumors has not been previously studied. This study aims to evaluate the diagnostic accuracy of MCT with and without dermoscopy and to describe the dermoscopic features of a large series of MCT. <b><i>Methods:</i></b> Dermoscopic images of 161 MCT were evaluated. Clinical and dermoscopic imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To our knowledge, about 50 cases of BMT have been reported in the literature [ 1 , 3 6 ]; dermoscopy has been described in details in only 9 cases ( Table 1 ). One of the two tumors is usually recognized upon dermoscopy when one of the two component is prevalent, but usually the exact diagnosis of BMT is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, about 50 cases of BMT have been reported in the literature [ 1 , 3 6 ]; dermoscopy has been described in details in only 9 cases ( Table 1 ). One of the two tumors is usually recognized upon dermoscopy when one of the two component is prevalent, but usually the exact diagnosis of BMT is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Zaballos et al recently found that the most frequent CTs are: basal cell carcinoma (BCC)-seborrheic keratosis (37.9%), BCC-melanocytic nevus (19.9%), and melanoma-seborrheic keratosis (6.8%). 1 The collision BCC-melanoma is very rare (reported under the terms "basomelanocytic tumor (BMT)") and its dermoscopic features have been described in only few cases [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In eight studies, triple associated lesion was reported (e.g. melanoma–BCC–trichoblastoma) 8 . Frequent tumours in photodamaged skin such as actinic keratosis and solar lentigo are probably underreported.…”
Section: Discussionmentioning
confidence: 99%
“…melanoma-BCC-trichoblastoma). 8 Frequent tumours in photodamaged skin such as actinic keratosis and solar lentigo are probably underreported. We present a new association of a DPW with MIS.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of squamous cell carcinoma and melanoma in the same tumor (SMT) is a rare event; Zaballos et al 2 recently found that the most frequent collision tumors (CTs) are: basal cell carcinoma–seborrheic keratosis (37.9%), basal cell carcinoma–melanocytic nevus (19.9%), and melanoma–seborrheic keratosis (6.8%). Histologically, CTs may result from a variety of modality of “collisions” such as colonization, combined, biphasic, biphenotypic, or intermingled neoplasms.…”
mentioning
confidence: 99%